INOVASI PEMBERDAYAAN MASYARAKAT DI KAMPUNG KB NAGARI MUNGO - Yulizawati Yulizawati; Fuad Aufa Hasari; Suci Juliana; Miftahul Fikri; Nidia Irsada (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
West Indobaleh Family Planning Village, Nagari Mungo as a community empowerment innovation aimed at increasing the participation of families, communities, the role of government, non-governmental institutions and the private sector in carrying out KKBPK programs by the needs and conditions of the KB Kampung region in West Indobaleh, Nagari Mungo. The method used in this activity is documentary studies, interviews, and quantitative analysis. The results of the KB village data are the residents in West Indobaleh with a total of 1985 inhabitants. The data obtained included 72% of family heads and 28% of non-family members. Then the total number of fertile couples is 365 couples and 86 non-fertile couples. Then the number of residents who have used KB is 140 people, who are using KB 128 people, and those who have not used KB are 274 people. Then the data shows that of 173 households, there were 219 toddlers, of 289 family heads, there were 483 teenagers, and 131 family heads, there were 200 older people. The KB village is also one of BKKBN's work programs that can help the community to set priorities and help realize the goals to be achieved by the family, and to improve the quality of life of the city.